Bio-Reclamation Evaluation of Former Gold Mine Land: Pre- and Post-Reclamation Soil Management Conditions - Nuriman, Muhammad; Wibowo, Sigit Sapto; Rezekikasari, Rezekikasari; Agustine, Leony; Setiawati, Tia (Jurnal Biologi Tropis, 2025)
Former gold mining land, especially those abandoned without reclamation, experiences serious physical, chemical, and biological degradation, and is potentially contaminated with heavy metals such as mercury (Hg). This study aims to evaluate the effectiveness of organic farming-based bioreclamation and good soil management, using dwarf elephant grass (Pennisetum purpureum) and chicken manure in improving the condition of former gold mining land. The parameters analyzed include physical, chemical, and biological properties of the soil, as well as mercury levels in the soil and plants. The results showed that the soil quality index increased from 0.32 (low) to 0.62 (good). The organic C content increased from 0.91% to 2.16%, soil pH increased from 3.53 to 5.03, and the availability of phosphorus and potassium also increased. The population of methyl mercury-reducing bacteria increased 22.4 - 58.2 times, indicating improved microbial adaptation to the environment. Mercury content in plant tissue decreased drastically from 11.60 mg/kg to 0.11 mg/kg or a decrease of 99.05%, although still slightly exceeding the threshold. The conclusion is that reclamation with an organic approach and effective soil management not only improves soil fertility and quality, but also reduces the risk of heavy metal poisoning.